Social Development of Children Under-Five as the Impact of Extramarital Pregnancy - Purbanova, Reni; Demartoto, Argyo; Murti, Bhisma (Journal of Maternal and Child Health, 2017)
Background: Teenagers have a great curiosity of something have never been experienced before. This characteristic